(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: Autism spectrum disorder (ASD) is defined as neurological and developmental disorder with characteristic features that include delayed gross motor milestones. It can be recognized at the initial stage during infancy or childhood with major affection see in communication and behavioral response of the child. Every 1 child amongst 100 children suffers from autism in India. The aim of our study was to see the effects of bimanual exercises on the hand function and kinesthetic awareness in the child with autism spectrum disorder and the objective of the study was to measure kinesthetic awareness, to measure pegboard reaction time and to measure grip strength. Method: 20 children were selected on the basis of inclusion and exclusion criteria and were divided into 2 groups, interventional group (group A) and control group (group B), each group consisted of 10 children each. Group A has 6 boys and 4 girls and group B has 7 boys and 3 girls. A written consent was taken from the parent (guide) of autistic child and study was explained to them and data was collected and analyzed using SPSS within the confidence interval of 95%. Result: - On the basis of data analysis table no. 1 shows the prevalence of both the genders. And table no. 8 shows the comparison between interventional group and control group within the confidence interval of 95% (with significant p value- 0.02) Conclusion: Bimanual exercises has been shown to be effective in improving hand function and kinesthetic awareness in children suffering from Autism spectrum disorder.